Tervezéselméleti alapvetések - Faragó, László (Tér és Társadalom, 1997)
Fundamental theoretical approaches of regional planning are discussed in the study that are based chiefly on J. Friedmann's approach. Establishment and recognition of the need for modern spatial planning are discussed in terms of "socialist" (centrally planned) and market-based traditions. Planning is defined by the author as the analysis of main trends of the past and the future, specification of main directions of the future development and the range of devices required to reach them, arrangement of decisions and formulation of the action program furthermore, political context of the process must be pointed out as well. Three types of planning (the allocative, innovative and the radical one) are discussed in details. The author distinct five "manners" of planning according to their position in the planning system such as centralised, strategic, corporative and transactional planning furthermore, planning supported by social activity. In the last chapter, regional planning is put into the context of the structures described above.